Thermo-mechanical analysis of the DEMO FW module. (9th September 2015) - Igitkhanov, Yu; Fetzer, R; Boccaccini, L; Bazylev, B
Abstract: Thermomechanical performance of the first wall (FW) W/EUROFER sandwich type module is analyzed under DEMO reactor conditions. Engineering heat loads to the FW panels are estimated for steady state operation with the edge localized modes (ELMs). Calculations carried out by MEMOS code show the inhomogeneity of the material temperature due to discrete location of the water cooling tubes embedded into EUROFER. The hot spots are formed in the W armor and EUROFER between the cooling sectors and depend on the distance of their mutual locations. The bending stress due to vertical temperature gradients in W and EUROFER layers is calculated and remains smaller than the ultimate tensile stress for expected temperatures. Calculations show that under the Type I ELMs expected in DEMO the W surface melts at the ELMs peak positions and solidifies between ELMs. There is no temperature difference found between hot and cool spots during ELMs.